Impact of Unemployment on the Mental Health of Youth Living in Nabuti, Mukono District - Derrick Mpanga (Uganda Christian University, 2023)
The study analysed the impact of unemployment among the youth on their mental health in Nabutii in Mukono district. It specifically focused on; identifying the causes of unemployment among the youth in Nabuti, examining the effects of unemployment on mental health of the youth in Nabuti and identifying the measures that can be taken reduce the level of unemployment among the youth residing in Nabuti in Mukono district and hence improving their mental health. The study was conducted utilizing a cross-sectional survey research design that also included qualitative and quantitative research methods. Both purposeful and straightforward random sampling approaches were utilized to acquire the data through the use of questionnaires and interviews. The survey also included a sample of 50 participants, including young leaders, the chairman of LC1, residents of Nabuti between the ages of 25 and 35, and medical professionals from Mukono Health Centre IV. From the findings, it was revealed that youth unemployment’s complex causes include; limited job opportunities, inadequate education and skills training, and discriminatory hiring practices, with discrimination and skills-job mismatch being prominent issues. It emphasized the urgent need for mental health support for unemployed youth due to increased stress, anxiety, and depression. The study suggests a multifaceted approach, including vocational training, job creation, counseling, entrepreneurship promotion, industry-education partnerships, and mentorship, to address youth unemployment comprehensively and ensure both economic stability and the well-being of the region’s youth. Finally, the study recommended a multi-pronged approach to combat youth unemployment in Nabuti, Mukono district, including addressing job market discrimination, expanding vocational training and education, enhancing networking opportunities, creating job listing platforms, bridging the skills-job mismatch, providing tailored mental health support, promoting entrepreneurship, strengthening educational-industry partnerships, and establishing mentorship programs to empower and guide youth in their job search and career development.
This is a dissertation.